Effect of the inoculum/substrate ratio on the biochemical methane potential (BMP) of grape marc - Silva,Kessia Caroline Dantas da (2020)
Abstract The grape industrialization process produces large volumes of solid organic waste, with the grape bagasse being the main waste generated in the winemaking process. Anaerobic digestion can be used to treat and dispose of agro-industrial biomass waste. The objective of this study was to evaluate the effect of the inoculum/substrate ratio on the Biochemical Methane Potential (BMP) of grape marc. The experiment was performed in laboratory scale through a system of reactor bottles in batches, removing a set of triplicate flasks for sampling and analysis every 48 hours, with the test lasting 12 days. The reactors contained residue, inoculum and 20% of nutritive solution, maintaining 20% of headspace. The reactors were incubated in an incubator at a mesophilic temperature (35 ± 2°C) and shaken manually every 24 hours. Three different inoculum/substrate (I/S) ratios of 0.75, 1.5 and 3 were used to evaluate the methane yield, organic removals and at the end of degradation the morphology of the bacterial community was evaluated by means of scanning electron microscopy. The I/S 3 ratio provided the best results for loading anaerobic systems, indicating that grape marc presents potential for biological treatment through anaerobic digestion.